THE INFLUENCE OF WORK LIFE BALANCE, EMPLOYEE ENGAGEMENT, AND CAREER DEVELOPMENT ON TURNOVER INTENTION OF THE MILENNIAL GENERATION THE SPECIAL REGION OF YOGYAKARTA - Vissabella Mudita; Heri Prasetyo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The increasing dominance of the millennial generation in the Indonesian workforce presents both opportunities and challenges, especially related to high turnover intentions. In the Special Region of Yogyakarta (DIY), where millennials make up a large portion of the workforce, organizations face concerns about employee retention. This study aims to examine the simultaneous influence of work-life balance, employee engagement, and career development on turnover intentions among millennial workers in DIY. The approach used is quantitative explanatory, with data collection from 100 respondents aged 25–40 years using purposive sampling techniques. Data analysis was performed using multiple linear regression using SPSS. The results showed that the three independent variables simultaneously had a significant effect on turnover intention (R² = 0.820). However, partially only employee engagement and career development showed a significant positive effect, while work-life balance did not. The discussion shows that although work-life balance is often considered important, this factor may not be enough to retain millennials in the workplace without being mediated by job satisfaction or other variables. In contrast, strong work engagement and clear career development opportunities actually showed a high tendency for turnover—possibly due to greater expectations and mobility among millennial professionals. This finding emphasizes the importance of a comprehensive retention strategy, which is tailored to the values ​​and aspirations of the younger generation. Investment in opportunities for growth and meaningful engagement appears to be more effective than simply offering work flexibility.